Identification of contractual issues in agriculture process A dematel- based model - Manuel, Mojikon Melvin; Lee, Chia Kuang; Bujna, Marián; Ooi, Hai Lee (Penerbit Universiti Malaysia Pahang, 2024)
The agriculture sector contributes vastly to a nation’s economy, including Malaysia. Nevertheless, limited research has looked on the contractual issues in agriculture process. The purpose of this study was to explore the contractual issues in the agriculture process and determine the relationship between both variables. The respondents involved seven experts from the agriculture sector in Sabah, Malaysia and a survey questionnaire were used to gather the data. Subsequently, the DEMATEL method was used to create the causal and effect diagram between the contractual issues. The results showed that Delayed Delivery Issues (Issue A) is the most crucial contract issue in agriculture and must be addressed. Furthermore, the most crucial relationship existed between Crucial Contract Issues (Issue A) and Contract Duration (Issue E). These issues should be studied further to improve the agriculture sector.